2016
DOI: 10.1002/chem.201600448
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of Bright‐Fluorescent Soft Materials from Small Organic Molecules

Abstract: Highly fluorescent and biocompatible soft materials are desirable for many potential applications, but their synthetic processes are somehow complicated. Herein, we have explored the feasibility of synthesis of unconventional fluorescence soft materials from small organic molecules under mild conditions. A new blue-fluorescent soft material with high quantum yield (89.6 %) and eutectic feature prepared by simple heat treatment of citric acid (CA) and cysteine (Cys) aqueous mixtures below 100 °C in air was repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…[36] 2) Nitrogen-containing NTLs: amines [poly(amido amine) (PAMAM), [37,38] hyperbranched poly(amino ester) (PAE), [39,40] and poly(amino ether ester)], [41] imines [linear or hyperbranched polyethyleneimine (PEI)], [42][43][44] oximes (hexanal oximes), [11] nitriles [polyacrylonitrile (PAN)], [17] amides [polyacrylamide (PAAm), [45] poly(N-isopropylacrylamide) (PNIPAM), [32] poly(ether amide) (PEA), [46] poly(esteramide-ether) (PEAE), [47] and poly(amido acids)], [48] imides (polysuccinimide), [20,22] polyurethane, [49,50] amino acids, [51,52] and lactams [polyvinylpyrrolidone (PVP), [53] and poly(Nvinylcaprolactam) (PNVCL)]. [54] 3) Sulfur-containing NTLs: thiols (cysteine), sulfones (polysulfone), [55] sulfonic acids [perfluorosulfonate ionomers (PFSI)], [10] sulfonates [poly(4-vinylpyridine)butane-1sulfonate (PVP-S)], [56] and thiourea. [57] 4) NTLs with other atoms.…”
Section: Diversity Of Ntlsmentioning
confidence: 99%
“…[36] 2) Nitrogen-containing NTLs: amines [poly(amido amine) (PAMAM), [37,38] hyperbranched poly(amino ester) (PAE), [39,40] and poly(amino ether ester)], [41] imines [linear or hyperbranched polyethyleneimine (PEI)], [42][43][44] oximes (hexanal oximes), [11] nitriles [polyacrylonitrile (PAN)], [17] amides [polyacrylamide (PAAm), [45] poly(N-isopropylacrylamide) (PNIPAM), [32] poly(ether amide) (PEA), [46] poly(esteramide-ether) (PEAE), [47] and poly(amido acids)], [48] imides (polysuccinimide), [20,22] polyurethane, [49,50] amino acids, [51,52] and lactams [polyvinylpyrrolidone (PVP), [53] and poly(Nvinylcaprolactam) (PNVCL)]. [54] 3) Sulfur-containing NTLs: thiols (cysteine), sulfones (polysulfone), [55] sulfonic acids [perfluorosulfonate ionomers (PFSI)], [10] sulfonates [poly(4-vinylpyridine)butane-1sulfonate (PVP-S)], [56] and thiourea. [57] 4) NTLs with other atoms.…”
Section: Diversity Of Ntlsmentioning
confidence: 99%
“…Figure lists some of the most common moieties for the construction of organic fluorophores, like polycyclic aromatic hydrocarbons (PAH), aromatic amines, BODIPY, and fluorescein. With regard to the nonconventional luminogens, so far, more and more examples including molecular and macromolecular, synthetic and natural occurring compounds, such as PAMAM, PEI, starch, cellulose, bovine serum albumin (BSA), PAN, PNHSMA, glucose, poly(acryl acid) (PAA), perfluorosulfonate ionomers (PFSIs), and supramolecular systems are found . For each system, people try to identify the exact contributing moieties.…”
Section: Emission Sourcesmentioning
confidence: 99%
“…Generally, these polymers involve electron‐rich heteroatoms, such as nitrogen (N), oxygen (O), sulfur (S), phosphorus (P), and/or unsaturated C = C and C≡N subgroups. Apart from the most intensively investigated archetypal poly(amidoamine)s (PAMAM), other macromolecular nonconventional luminogens, such as poly(amino ester)s (PAE), poly(ether amide)s (PEA), polyacrylonitrile (PAN), poly( N ‐vinylpyrrolidone) (PVP), polyethylenimines (PEI), polyureas (PU), sulfonated acetone–formaldehyde (SAF) condensates and derivatives, poly( N ‐hydroxysuccinimide methacrylate) (PNHSMA), polysiloxanes, and even supramolecular assemblies have been becoming increasingly eye‐catching owing to their unique intrinsic emissions. Compared with conventional luminophors, they normally enjoy the advantages of good hydrophilicity, facile preparation, environment‐friendliness, outstanding biocompatibility, and so forth, which render them highly suitable for biological and medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…These studies followed pioneering work of Yang’s group, who identified the fluorescent citrazinic acid derivative 5-oxo-1,2,3,5-tetrahydroimidazo [1,2-α] pyridine-7-carboxylic acid (denoted as IPCA) as the major luminescent component formed during the hydrothermal synthesis of CDs from CA and ethylenediamine 40 . This and another brightly luminescent molecular fluorophore of a similar structure, namely as 5-oxo-2,3-dihydro-5H-[1,3]-thiazolo[3,2-a]pyridine-3,7-dicarboxylic acid (TPDCA) 41 have been reported as components of fluorescence biodegradable polymers 42,43 , and other kinds of soft composite materials 4447 .…”
Section: Introductionmentioning
confidence: 99%